Structural Policy for Industry: Principles, Criteria, Priorities and Priority Calculation Method - Balčiūnas, Norbertas (Ekonomika, 1997)
In this paper structural policy methodology and it’s components are investigated: prerequisites, principles, criteria, and priorities.Natural resources of Lithuania, skill structure of the labour force, means of production, and the level of the engineering process are dislocated through prerequisites. The definition of the structural policy for Lithuanian industry is submitted. The principles of the structural policy include labour division and cooperation, natural resources and their opportunities for conservation, and the commodity market and capital spheres. The criteria include employment of the population, a demand for resources and efficiency of their utilisation, an increase in national product and labour productivity, science-intensive production and its competitiveness level in the market, and environmental safety.The priority calculation method developed by the author is being published for the first time in this paper as well as three axioms of the structural policy for sectoral restructuring and the development of industry.